Frequency of Urinary Stress Incontinence in Women after Vaginal Delivery - Amber Naeem, Nisa Mohsin, Anila Mujadid Qureshi, Aamna Salman, Sarwat Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Stress urinary incontinence is defined as involuntary loss of urine on physical exertion like coughing, sneezing, laughing or jumping. This condition in women is very distressing and it is usually kept disguised, so women remain untreated. This condition also causes feeling of inferiority and depression. There are different risk factors identified in causing urinary stress incontinence like constipation, traumatic and operative vaginal births, pelvic organ prolapse, abdominal mass, smoking, obesity, old age and menopause. The present study is design to know the actual magnitude of stress incontinence. There by strategies could be devised to reduce this morbidity. Objective: To determine the frequency of urinary stress incontinence in women after vaginal delivery Setting: This study was conducted at ISRA University Hospital, Hyderabad. Duration: Six months from Jan 2020 to June 2020. Design: Descriptive cross sectional. Subject and Methods: There were 141 women with history of urinary incontinence within 40 days of vaginal delivery were included in this study. Patient who fulfill the inclusion and exclusion criteria and came within forty days after vaginal delivery. The final outcome that is urinary stress incontinence was labeled as positive or negative on approved proforma. Results: The average age of the patients was 26.75±5.72 years. Frequency of urinary stress incontinence in women after vaginal delivery was observed in 14.18% (20/141). Conclusion: Results of this study suggest that the mechanical strain during labor may add to the risk associated with pregnancy itself. Prenatal counseling about routes of delivery should provide a balanced account of the advantages and disadvantages for mother and child. The information from this study provides important information for clinicians, patients, and policymakers regarding childbirth and incontinence. Keywords: Stress Urinary Incontinence, Vaginal Delivery, Operative Vaginal Birt